Illustrated dictionary of health and nutrition terms, definitions, examples (3G E-Learning LLC, 2018)
This illustrated dictionary provides concise definitions and explanations of health and nutrition terms together with state-of-the-art scientific and practical terms, presented in an easy-to-use, A-Z order with pictures and figures as well as examples are given to clarify the terms. It is a perfect tool for understanding of health and nutrition terms for Higher Secondary to Undergraduate students and improving their spelling and grammar. --Publisher